Media Puzzle Untuk Meningkatkan Kerjasama Dan Hasil Belajar Dalam Pelajaran Bahasa Indonesia - Ika Cahyaningtyas; Wahdan Najib Habiby; Andi Arfianto (Departement of Mathematics Education, 2024)
Learning activities in class V require strategies that take into account the characteristics of students' development at that stage. In this context, puzzle media was chosen as the focus of research because it has the potential to integrate learning based on cooperation and interaction between students. The aim of this learning improvement research is to improve cooperation and learning outcomes for class V students at SD Muhammadiyah PK Kottabarat in Indonesian Language lessons. This type of research is classroom action research with subjects of 28 students in class VB. The minimum competency criteria score at this school is 80. Research activities include planning, action, observation and reflection. Data collection uses observation and tests. The results of the research in cycle I were the percentage of learning completeness was 64% with an average learning outcome value of 75.7. In cycle II there was an increase, namely with a learning completeness percentage of 100% with an average learning outcome score of 87. From the results of the assessment recapitulation, 7 groups experienced an increase with details of 5 groups being very good at cooperation between students and 2 groups also being good at cooperation between students. So improving learning by using puzzle media has succeeded in improving learning outcomes and increasing collaboration between students to complete the tasks given. Learning Indonesian using puzzle media in the VB class at SD Muhammadiyah PK Kottabarat is very effective in improving student learning outcomes and also increasing collaboration between students. The choice of puzzle media used by researchers is also able to hone students to think critically.